Relevance of ELF speakers’ source speeches: interpreters’ interventions - Albl-Mikasa, Michaela (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2023)
In their capacity as language experts, interpreters are sometimes expected to deliver target texts that are better than their underlying source text, especially when the latter was produced by a speaker in a language that is not their L1. The spread of global English has given rise to ever more occasions when interpreters encounter non-L1 speakers of English as a lingua franca (ELF). The question as to whether or not interpreters try to optimise those speakers’ input is addressed by applying Relevance Theory (RT) as a conceptual and methodological framework that helps to understand interpreters’ needs or readiness to augment relevance for their audience. The paper builds on data from the larger project CLINT (Cognitive Load in Interpreting and Translation). The 56 renditions by all 28 professional interpreters participating in the project’s interpreting part of two original ELF speaker texts and their edited versions are analysed with a view to the enrichment processes undertaken by the interpreters. A comparison of the renditions of the original versus edited versions of the two texts shows that interpreters do engage in such processes considerably more when rendering ELF texts, especially if they are technical in nature. Determining whether or not these interventions lead to actual cognitive effects in terms of information gains on the part of the audiences or to increased cognitive effort on the part of the interpreters requires additional comprehension testing and triangulation with other indicators of cognitive effort.